2011
DOI: 10.1371/journal.pone.0024559
|View full text |Cite
|
Sign up to set email alerts
|

Siglecs Facilitate HIV-1 Infection of Macrophages through Adhesion with Viral Sialic Acids

Abstract: BackgroundHuman immunodeficiency virus type 1 (HIV-1) infects macrophages effectively, despite relatively low levels of cell surface-expressed CD4. Although HIV-1 infections are defined by viral tropisms according to chemokine receptor usage (R5 and X4), variations in infection are common within both R5- and X4-tropic viruses, indicating additional factors may contribute to viral tropism.Methodology and Principal FindingsUsing both solution and cell surface binding experiments, we showed that R5- and X4-tropic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
85
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(93 citation statements)
references
References 52 publications
4
85
4
Order By: Relevance
“…Several types of pathogens can exploit sialic acids, which are either synthesized by themselves or acquired from the host, to activate inhibitory Siglecs on innate immune cells, thus attenuating host protective responses and achieving immune evasion [11]. Membrane Siglec1 has been reported to be utilized by HIV-1 to infect macrophages [29]. Together with our data that Siglec1 expression was upregulated upon viral infection, we thus speculate that Siglec1 upregulation may be an important and common strategy utilized by different families of viruses to evade host immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…Several types of pathogens can exploit sialic acids, which are either synthesized by themselves or acquired from the host, to activate inhibitory Siglecs on innate immune cells, thus attenuating host protective responses and achieving immune evasion [11]. Membrane Siglec1 has been reported to be utilized by HIV-1 to infect macrophages [29]. Together with our data that Siglec1 expression was upregulated upon viral infection, we thus speculate that Siglec1 upregulation may be an important and common strategy utilized by different families of viruses to evade host immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…A key question to be addressed is whether this pathway has an important role in HIV infection and spread in vivo since sialoadhesin is not normally expressed on DCs but is restricted to subsets of inflammatory monocytes and tissue macrophages 21 . In this regard, HIV can also interact with other Siglecs, including Siglec-3, Siglec-5, Siglec-7 and Siglec-9 via sialylated gp120, also promoting infection of macrophages 46 …”
Section: Siglecs and Infectionsmentioning
confidence: 99%
“…In DCs, Siglec-1 serves as a receptor for capturing HIV-1 through its Ig-like V set domain by binding to host-derived glycosphingolipid (ganglioside GM3) that is incorporated in the membrane of HIV-1 particles. This interaction between Siglec-1 and GM3 is independent of the HIV envelope protein [22] , while in macrophages the capture of HIV-1 is through the interaction of Siglec-1 and HIV-1 envelope protein [15,16] . Studies have shown that Siglec-1 expression is influenced by the cytokines present in the environmental milieu induced as a result of chronic inflammation [23,24] .…”
Section: Research Highlightmentioning
confidence: 97%
“…However, unlike CD4+ T cells, macrophages and monocyte-derived macrophages express relatively low levels of CD4 on the cell surface further confounding the role of this molecule in HIV-1 entry into macrophages. Recently, the role of sialic acid-binding immunoglobulin-like lectin-1 (Siglec-1) in HIV-1 infection of myeloid cells has been investigated, and shown to play an important role in HIV-1 pathogenesis in both dendritic cells [13,14] and macrophages [15,16] . This highlight will focus on (i) the effect of environmental milieu on Siglec-1 expression on macrophages, (ii) the role of Siglec-1 in HIV-1 infection of macrophages, and (iii) the interaction of Siglec-1 with the virus envelope.…”
Section: Research Highlightmentioning
confidence: 99%